Analysis and Comparison of Whole Slide Imaging System Guidelines in Japan, the United States, and Europe - Yasuhiro Taniguchi; Manabu Tamura; Ken Masamune (Tokyo Women's Medical University Journal)
Background: This study aimed to analyze the characteristics and challenges of whole slide imaging (WSI) system guidelines in Japan, the United States, and Europe. Methods: Information disseminated by academic societies in Japan, the United States, and Europe was extracted from their websites, and the WSI system guidelines were identified. Based on the classification criteria, the guidelines were grouped into six categories, and their characteristics and issues were analyzed through comparison. Results: A total of 24 guidelines were identified: eight in Japan, 12 in the United States, and four in Europe. The first WSI system guidelines were issued in the United States, and only one was issued by a regulatory authority. While the guidelines in the United States and Europe cover all six categories, those in Japan lack coverage of funding strategies. Conclusions: WSI system guidelines in the United States contribute to establishing regulatory and technical requirements for the clinical use of the WSI system in Japan, the United States, and Europe. This study also suggests directions for funding strategies that could contribute to the widespread adoption of WSI systems in Japan, such as monetization through joint research with companies and the utilization of grants.